2014
DOI: 10.1186/1880-6805-33-8
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and psychological responses of young males during spring-time walks in urban parks

Abstract: BackgroundIt is widely believed that contact with the natural environment can improve physical and mental health. Urban green spaces may provide city residents with these benefits; however, there is a lack of empirical field research on the health benefits of urban parks.MethodsThis field experiment was performed in May. Seventeen males aged 21.2 ± 1.7 years (mean ± standard deviation) were instructed to walk predetermined 15-minute courses in an urban park and a nearby city area (control). Heart rate and hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
101
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 34 publications
15
101
3
1
Order By: Relevance
“…These findings are consistent with studies showing that positive emotion is the first to appear when humans encounter a natural environment [34]. They are also consistent with previous findings showing that when humans are in a natural environment, negative emotions will decrease while positive emotions will increase [13,17,20,27,[35][36][37][38].…”
Section: Categories Descriptionsupporting
confidence: 93%
“…These findings are consistent with studies showing that positive emotion is the first to appear when humans encounter a natural environment [34]. They are also consistent with previous findings showing that when humans are in a natural environment, negative emotions will decrease while positive emotions will increase [13,17,20,27,[35][36][37][38].…”
Section: Categories Descriptionsupporting
confidence: 93%
“…According to the SDM questionnaire scores, older women felt more “comfortable” and “relaxed” after carrying out the plant activity than after carrying out the control activity. These results, which show the psychological benefits of gardening, are partly related to findings from previous research carried out in forests regarding the positive effect of nature on humans . Thus, the psychological benefits of gardening include improved mood state in older adults, and are expected to play a very important role in improving mental health in the future.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies have focused on the physiological relaxing effects of nature-derived stimulation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], and there are several reports on the effects of wood odor on humans [9][10][11]. Miyazaki et al [9] reported that inhalation of Taiwan hinoki oil odor decreases systolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%